Analysis of Samyang Instant Noodle’s Market in Indonesia Using The Impact of Uncertainty Avoidance by Hofstede's Cultural Dimensions - Septyanto Galan Prakoso; Randhi Satria; Nesya Cesari Kinanti; Retnaningtyas Puspitasari (Insignia: Journal of International Relations, 2019)
Abstract Indonesia as the second-largest country in consuming instant noodles in the world surely enacts it to become a lucrative market for instant noodle manufacturers, including Samyang Foods from South Korea. The emerging popularity of the Korean Wave or Hallyu Wave has further encouraged the penetration of Samyang Foods products into the palate of Indonesia people. However, the issue of the halal logo on Samyang instant noodles began to arise in 2016 and this affected the sale of Samyang Foods products in Indonesia, bearing in mind 85% of Indonesians are Muslim. The issue of a halal label on Samyang instant noodle is indeed a worthy event to be researched and discussed. This article will talk about the impact of uncertainty avoidance in the acceptance of Samyang instant noodles by Indonesian people and the potential market of Indonesian instant noodle for Samyang Foods. The subject that the author examines is through journals article, books, official sites, and internet articles. A qualitative descriptive method is used by the author to analyze the case. The result of this study is expected to provide an overview of the uncertainty avoidance’s contribution to the acceptance of Samyang instant noodles by Indonesian people. Indonesian instant noodle market will be elaborated with the consideration of uncertainty avoidance aspects, such as trust and loyalty. In conclusion, this article shows that uncertainty avoidance has a significant impact on Samyang instant noodle consumption in Indonesia and serves the analysis of the huge potential for the market expansion of Samyang Foods. Keywords: halal label, Indonesia, Samyang instant noodle, Samyang Foods. Abstrak Indonesia sebagai negara kedua terbesar dalam konsumsi mi instan di dunia, menjadikannya sebagai pasar yang menggiurkan bagi produsen mi instan, tak terkecuali Samyang Foods dari Korea Selatan. Meningkatnya popularitas budaya Korea Selatan atau yang dikenal sebagai gelombang Hallyu, semakin mendorong penetrasi masuknya produk Samyang Foods ke dalam selera masyarakat Indonesia. Namun isu logo halal pada produk mi instan Samyang mulai mencuat di masyarakat pada tahun 2016 dan hal tersebut berpengaruh pada penjualan produk Samyang Foods di Indonesia, mengingat 85% penduduk Indonesia menganut agama Islam. Permasalahan mengenai label halal pada mie instan Samyang adalah salah satu topik yang layak untuk diteliti dan didiskusika lebih lanjut. Artikel ini akan membahas mengenai dampak dari uncertainty avoidance terhadap konsumsi mie instan Samyang oleh masyarakat Indonesia dan potensi yang dimiliki pasar mie instan Indonesia bagi Samyang Foods. Topik dalam artikel ini diteliti berdasarkan data dan informasi dari berbagai artikel jurnal, buku, laman resmi, dan artikel internet. Sedangkan dalam analisis penelitian, penulis menggunakan deskriptif-kualitatif untuk menganalisis permasalahan yang diangkat. Hasil dari penelitian ini diharapkan dapat memberikan gambaran mengenai kontribusi konsep uncertainty avoidance terhadap keputusan konsumsi mie instan Samyang masyarakat Indonesia. Potensi pasar mie instan di Indonesia tersebut disajikan dengan mempertimbangkan aspek-aspek yang terkandung dalam konsep uncertainty avoidance, seperti kepercayaan dan loyalitas. Dengan demikian, artikel ini menyimpulkan bahwa uncertainty avoidance memiliki dampak yang signifikan terhadap keputusan konsumsi mie instan Samyang oleh masyarakat Indonesia dan adanya potensi besar atas pasar mie instan di Indonesia bagi Samyang Foods. Kata kunci: label halal, Indonesia, mie instan Samyang, Samyang Foods